1988
DOI: 10.1111/j.1476-5381.1988.tb11723.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the binding of [3H]‐CGS 19755: a novel N‐methyl‐d‐aspartate antagonist with nanomolar affinity in rat brain

Abstract: 1 CGS 19755 (cis-4-phosphonomethyl-2-piperidine carboxylic acid), a rigid analogue of 2-amino-5-phosphonopentanoic acid (AP5), is one of the most potent competitive N-methyl-D-aspartate (NMDA) antagonists described. Using Triton-treated crude synaptic membranes from rat [3H]-CPP (34-±)2-carboxypiperazin-4-yl)propyl-1-phosphonic acid), the corresponding analogue of 2-amino-7-phosphonoheptanoic acid (AP7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(49 citation statements)
references
References 13 publications
3
45
1
Order By: Relevance
“…In contrast to this finding, the block induced by 0.7 M CGS-19755, a competitive antagonist at the glutamate recognition site of the NMDA receptor (Murphy et al, 1988;Aizenman and Hartnett, 1992), was observed to increase slightly but significantly ( p Ͻ 0.01, ANOVA) with development in a total of 69 additional neurons tested at 13-30 DIV (Fig. 1 D, inset).…”
Section: Changes In Nmda Receptor Subunit Expression In Cultured Cortcontrasting
confidence: 43%
“…In contrast to this finding, the block induced by 0.7 M CGS-19755, a competitive antagonist at the glutamate recognition site of the NMDA receptor (Murphy et al, 1988;Aizenman and Hartnett, 1992), was observed to increase slightly but significantly ( p Ͻ 0.01, ANOVA) with development in a total of 69 additional neurons tested at 13-30 DIV (Fig. 1 D, inset).…”
Section: Changes In Nmda Receptor Subunit Expression In Cultured Cortcontrasting
confidence: 43%
“…In the present study, 3H-CPP poorly labeled NMDA receptors in regions that contain predominantly NR2B mRNA (e.g., striatum and lateral septum); however, in other studies (Monaghan, Beaton, and Larson, unpublished observations) we have found that the antagonist 3H-CGP39653 binds with low affinity in regions containing NR2B mRNA (e.g., striatum, septum). Taken together, these findings suggest that the high-affinity antagonist binding site (Murphy et al, 1988;Porter et al, 1992;vanAmsterdam et al, 1992;Benke et al, 1993) represents NR2A-containing NMDA receptors while the low-affinity radiolabeled antagonist binding site represents NMDA receptors that contain NR2B subunits.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the IC50s for both drugs were above the observed K,s for these drugs measured in radioligand binding experiments (Olverman et al, 1984;Murphy et al, 1988). NMDA receptor stimulation might cause activation of a positive feedback loop in which glutamate stimulates the release of endogenous NMDA agonist (presumably, but not necessarily, glutamate), generating a non-linear relationship between receptor occupancy and toxicity .…”
Section: Discussion Glutamine Toxicity In Astrocyte-poor Cultures Ismentioning
confidence: 94%